LITHOLOGY AND RESERVOIR IDENTIFICATION IN THE “EL” WELL, EAST JAVA USING SEISMIC INVERSION - Maulana Yusuf Ibrahim; Salma Dita Rysqi Puspita; Zhafirah Nurul Syarafina; Shaska Ramadhan Zulivandama; Eleonora Agustine (BULLETIN OF THE MARINE GEOLOGY, 2023)
The acoustic impedance inversion seismic method, carried out at the "EL" well in East Java,provides a description of the physical properties of subsurface rocks. This method involves identifying rocklayers, lithology types, porosity values, the presence of hydrocarbons, and fluids in the target zone usingboth well data and integrated seismic data. The data processing included the cross-plotting of acousticimpedance (AI) with gamma ray logs, porosity logs, and resistivity logs. We integrated seismic and welldata, picked horizons, and created AI inversion models. The based model inversion technique was used tocompare the synthetic model with the seismic data, aiming to obtain an AI value that closely represents theactual model. AI seismic inversion effectively separates lithological boundaries vertically and laterally,based on the selected picking horizon and created model. To enhance understanding of the lithology andhydrocarbon prospect zone in the study area, a cross-plot analysis was used to correlate the seismic inversionmodel. The results reveal that the study area represents a hydrocarbon prospect zone, with reservoir rocksconsist of coral and foram at a depth range of 2320 - 2430 ft.